1991
DOI: 10.1139/b91-052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hebeloma arenosa and phosphorus fertility on root acid phosphatase activity of red pine (Pinus resinosa) seedlings

Abstract: The ectomycorrhizal fungus Hebeloma arenosa Burdsall, MacFall & Albers was assayed for surface-accessible acid phosphatase activity in vitro on roots of red pine (Pinus resinosa Ait.) seedlings. Hebeloma arenosa was grown in defined liquid media containing 0, 17, 34, 68, or 136 mg/L phosphorus for 4 weeks. When assayed for acid phosphatase activity with p-nitrophenyl phosphate, 7.3 μmol of orthophosphate were released per gram dry weight of fungal tissue. There was no effect of added P on enzyme activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The acid phosphatase activity expressed in short roots and radicles was considerably lower than in corresponding S. bovinus mycorrhizal tissues. These data are in agreement with the earlier findings of MacFall & Slack (1991) and Pasqualini, Panara & Antonielli (1992) regarding acid phosphatase activities in mycorrhizal and non-mycorrhizal Pinus pinea and Pinus resinosa grown in pot cultures. The acid-phosphatase activity of P. involutus mycorrhizas was low in the current study, although higher than that detected in short roots.…”
Section: supporting
confidence: 93%
“…The acid phosphatase activity expressed in short roots and radicles was considerably lower than in corresponding S. bovinus mycorrhizal tissues. These data are in agreement with the earlier findings of MacFall & Slack (1991) and Pasqualini, Panara & Antonielli (1992) regarding acid phosphatase activities in mycorrhizal and non-mycorrhizal Pinus pinea and Pinus resinosa grown in pot cultures. The acid-phosphatase activity of P. involutus mycorrhizas was low in the current study, although higher than that detected in short roots.…”
Section: supporting
confidence: 93%
“…In many studies on ectomycorrhizae phosphatase activity is measured in in vitro cultures of the fungus or in excised mycorrhizal short roots (Alexander and Hardy, 1981;McFall et al, 1991). In contrast, the filter paper method allows determination of acid phosphatase activity in intact mycorrhizal root systems.…”
Section: Resultsmentioning
confidence: 99%
“…Plants can use organic P efficiently after the enzymatic hydrolysis to inorganic phosphate (Tarafdar & Claassen 1988) by phosphatase enzymes that are released by roots and microorganisms in the rhizosphere (Das et al 2014). There is little information concerning the effect of root phosphatase activity on the growth and physiology of tropical forest tree species (Kroehler & Linkins 1988, MacFall et al 1991, and data on balsa could not be found.…”
Section: Introductionmentioning
confidence: 99%